Effects of short-term combination therapy with insulin on glycoregulation and insulin secretory function in patients with type 2 diabetes mellitus and secondary failure to treatment with oral antidiabetic agents - Aleksandra Grbić; Gabrijela Malešević; Slavko Grbić; Milorad Grujičić; Vesna Jelača (Биомедицинска истраживања, 2019)
Introduction: Secondary failure to treatment with oral antidiabetic agents is defined as the absence of a favorable reaction to the oral therapy which had proved effective in the previous course of the treatment. The aim of the study is to investigate the residual effects of the short-term combination therapy with insulin on glycoregulation and insulin secretory function. Methods: The sample comprised 53 patients with type 2 diabetes mellitus (DM2) and secondary failure to treatment with oral antidiabetic agents who had been receiving combination therapy (basal insulin plus metformin) for three months. Following the evaluation of acute effects of insulin therapy, the patients had been receiving oral antihyperglycemic medications, used at the time of secondary failure, for three months, after which the residual effects of insulin therapy were estimated. Results: Three-month combination therapy significantly improved glycoregulation (fasting glycemia: 9.4 mmol/l vs. 6.1 mmol/l; postpransial glycemia: 11.5 mmol/l vs. 7.3mmol/l; daily glycemic profile: 10.0 mmol/l vs. 7.2 mmol/l) and insulin secretory parameters (insulinemia: 16.63 mU/l vs. 10.8 mU/l; C-peptid: 1.53 mg/ml vs. 1.81 mg/ml) compared with the period when secondary failure to oral therapy was observed (acute effects). Three months after the insuline therapy, glycoregulation and insulin secretory function were slightly poorerresidual effects (glycemia: 7.1mmol/l; postpransial glycemia: 8.3 mmol/l; daily glycemic profile: 8.4mmol/l; insulinemia: 13.3mU/l; C-peptid: 1.72 mg /ml). Conclusion: The reinclusion of oral antidiabetic agents after short-term insulin therapy led to mild deterioration in insulin secretory function. Nevertheless, all observed parameters of metabolic status were significantly better compared with the period prior to short-term use of insulin.
Keywords: type 2 diabetes mellitus; secondary failure of oral antidiabetic agents; combination therapy; C-peptide; insulin